Encyclopedia of insects - Resh, Vincent H. (Elsevier/Academic Press, 2009)
"Awarded Best Reference by the New York Public Library (2004), Outstanding Academic Title by CHOICE (2003), and AAP/PSP 2003 Best Single Volume Reference/Sciences by Association of American Publishers' Professional Scholarly Publishing Division, the first edition of Encyclopedia of Insects was acclaimed as the most comprehensive work devoted to insects. Covering all aspects of insect anatomy, physiology, evolution, behavior, reproduction, ecology, and disease, as well as issues of exploitation, conservation, and management, this book sets the standard in entomology." "The second edition of this reference will continue the tradition by providing the most comprehensive, useful, and up-to-date resource for professionals. Expanded sections in forensic entomology, biotechnology and Drosphila, reflect the full update of over 300 topics. Articles contributed by over 260 high profile and internationally recognized entomologists provide definitive facts regarding all insects from ants, beetles, and butterflies to yellow jackets, zoraptera, and zygentoma."--BOOK JACKET